1994
DOI: 10.1016/0014-5793(94)01165-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymannosylation to asparagine‐19 in hen egg white lysozyme in yeast

Abstract: Complementary DNA encoding hen egg white lysozyme (HEWL) was subjected to site-directed mutagenesis to have the N-glycosylation signal sequence (Asn"-Ty? '-Th?) by substituting Arg with Thr at position 21. The mutant lysozyme (R2lT) was expressed in Succharomyces cerevisiae carrying the yeast expression plasmid inserting the mutant HEWL cDNA. The mutant lysozyme was expressed in the glycosylated forms which are mainly a polymannosyl form with a small amount of oligomannosyl form. The polymannosyl lysozyme wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…As expected, a large amount of polymannosyl lysozyme was predominantly secreted in the yeast medium (Nakamura et al, 1993a). We were successful in constructing a single polyannosyl lysozyme at positions 19 and 49, and double polymannosyl lysozyme at both positions 19 and 49 (Kato et al , 1994). As shown in Fig.…”
Section: Polymannosyl Lysozyme Constructed By Genetic Modificationmentioning
confidence: 90%
See 1 more Smart Citation
“…As expected, a large amount of polymannosyl lysozyme was predominantly secreted in the yeast medium (Nakamura et al, 1993a). We were successful in constructing a single polyannosyl lysozyme at positions 19 and 49, and double polymannosyl lysozyme at both positions 19 and 49 (Kato et al , 1994). As shown in Fig.…”
Section: Polymannosyl Lysozyme Constructed By Genetic Modificationmentioning
confidence: 90%
“…To further elucidate the molecular mechanism of the improvement of functional properties of proteins by attachment with polysaccharide, genetic glycosylation of lysozyme was successfully attempted using the yeast expression system (Nakamura et al, 1993a(Nakamura et al, , 1993bKato et al, 1994;Shu et al, 1998;Kato et al, 1996). In yeast cells, the proteins having an Asn-X-Thr/Ser sequence are N-glycosylated in the endoplasmic reticulum and the attached oligosaccharide chain can be elongated with further extension of a large polymannose chain in the Golgi apparatus.…”
Section: Polymannosyl Lysozyme Constructed By Genetic Modificationmentioning
confidence: 99%
“…These results were consistent with other previous reports. Indeed influenza virus hemagglutinin (Wen and Schlesinger, 1984), envelope glycoprotein from Epstein-Barr virus (Schultz et al, 1987), lysozyme (Nakamura et al, 1993; Kato et al, 1994) and Geotrichum candidum lipase I1 (Vernet et al, 1993) have been shown to be hypergl ycosylated when expressed in S. cerevisiue. The N-linked mannan prevented recognition by polyclonal antibodies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the glycosylated lysozymes can be secreted in the yeast carrying the lysozyme cDNA having N ‐linked glycosylation signal sequence (Asn‐X‐Ser) by site‐directed mutagenesis. Interestingly, the secretion amounts are greatly increased compared with the wild‐type lysozyme and keep the soluble form even on heating up to 95°C [8,9]. This suggests the possibility of the high secretion of unstable mutants which are poorly secreted in yeast expressing system.…”
Section: Introductionmentioning
confidence: 99%